2021
DOI: 10.1107/s1600577520014666
|View full text |Cite
|
Sign up to set email alerts
|

High-speed rotating device for X-ray tomography with 10 ms temporal resolution

Abstract: The temporal resolution of X-ray tomography, using a synchrotron radiation X-ray source, has been improved to millisecond order in recent years. However, the sample must be rotated at a speed of more than a few thousand revolutions per minute, which makes it difficult to control the environment around the sample. In this study, a high-speed rotation device has been developed, comprising two synchronized coaxial motors movable along the direction of the axis, which can stretch or compress the rotating sample. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Recently, dynamic 4D observation has also become possible. Figure 7 demonstrates 4D X-ray CT with a temporal resolution of 10 ms for the process of breaking rubber while pulling it [41,42]. The upper left pad of Figure 7 shows a schematic illustration of the rotating device for the 4D X-ray CT.…”
Section: Cmos Cameramentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, dynamic 4D observation has also become possible. Figure 7 demonstrates 4D X-ray CT with a temporal resolution of 10 ms for the process of breaking rubber while pulling it [41,42]. The upper left pad of Figure 7 shows a schematic illustration of the rotating device for the 4D X-ray CT.…”
Section: Cmos Cameramentioning
confidence: 99%
“…Figure 7. Real-time 4D observation of rubber tensile fracture process (10-ms temporal resolution)[41,42]. Upper: rotation device for high-speed X-ray CT, lower: 4D tomograms of tensile fracture process of rubber.…”
mentioning
confidence: 99%
“…Our current imaging system is not optimized for fast shutter speed, < 1 ms, and high image frame rate, >100 Hz (Mokso et al, 2017). Moreover, the current sample rotation mechanism for tomography cannot operate at high speed to take advantage of the 1 ms exposure (Mashita et al, 2021).…”
Section: Potential Improvementsmentioning
confidence: 99%
“…For example, it was reported that the cavities formed during the fracture of a material improve its resistance to further fracture owing to the release of polymer constraints between cavities (Ishikawa & Chiba, 1990). Although the macroscopic fracture phenomenon has been examined using electron microscopy, X-ray tomography and mechanical measurements (Bayraktar et al, 2008;Uesugi et al, 2016;Mashita et al, 2021), few studies have focused on the changes in polymer dynamics associated with stress concentration and release at the molecular scale. Understanding the stress-producing phenomenon over a wide range (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in the mechanical strength and resistance to fracture are required in numerous rubber products. It is therefore desirable to clearly understand the microscopic fracture mechanism of rubber, and so considerable research has been conducted on the fracturing of polymer materials (Ishikawa & Chiba, 1990;Bayraktar et al, 2008;Uesugi et al, 2016;Mashita et al, 2021;Choi et al, 2012;Naoki et al, 1974;Nakajima et al, 1978;Diaz-Calleja et al, 1987;Munch et al, 2006;Boyer, 1968;Engels et al, 2012;Retting, 1970;Kalfoglou & Williams, 1972;Suzuki et al, 2019). For example, it was reported that the cavities formed during the fracture of a material improve its resistance to further fracture owing to the release of polymer constraints between cavities (Ishikawa & Chiba, 1990).…”
Section: Introductionmentioning
confidence: 99%